Analisis Pengaruh Manajemen Perpajakan Terhadap Penerimaan Pajak Daerah Pada Badan Pendapatan Daerah Kabupaten Sidrap - Misbahuddin Misbahuddin; Nashriah Akil (STIM-LPI Makassar, 2021)
The aim of the study was to: 1) analyze the effect of Management and Organizational Structure to Local Tax Revenue at the Department of Revenue Regency of Sidrap, 2) analyze the effect of Organizational Procedures to Local Tax Revenue at the Department of Revenue Regency of Sidrap 3) analyze the effect of Organizational Strategy to Local Tax Revenue at the Department of Revenue Regency of Sidrap, 4) analyze the effect of Management and Organizational Culture to Local Tax Revenue at the Department of Revenue Regency of Sidrap, 5) analyze the effect of Tax Administration Reform which includes the organizational structure, procedures Organizations, Organizational Strategy and Modernisation of the organizational culture to Local Tax Revenue at the Department of Revenue Regency of Sidrap The study was condute at the Department of Revenue Regional Regency of Sidrap. Sample was the Systematic random sampling with 44 employees as samples. Analysis of the data in this study using validity test, reliability test, and multiple linear regression analysis. The result of study indicates that 1) Organizational Structure has positive and significant influence to Local Tax Revenue at the Department of Revenue Regency of Sidrap, 2) Management and Organizational Procedures has positive and significant influence to Local Tax Revenue at the Department of Revenue Regency of Sidrap 3)Management and Organizational Strategy has positive and significant influence to Local Tax Revenue at the Department of Revenue Regency of Sidrap, 4) Modernisation of the management and organizational culture has positive and significant influence to Local Tax Revenue at the Department of Revenue Regency of Sidrap, 5) Tax Administration Reform which includes the organizational structure, procedures Organizations, Organizational Strategy and Modernisation of the organizational culture simultaneously have significant influence to Local Tax Revenue at the Department of Revenue Regency of Sidrap.